New insights into repurposing of renin-angiotensin system inhibitors against Alzheimer’s disease - Sunita Mishra, Swagata Pattanaik, Sonali Sahoo, Shakti Ketan Prusty, Pratap Kumar Sahu, Debajyoti Das (Journal of Applied Pharmaceutical Science, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by a complex and multidimensional pathology, including amyloid-β plaques, hyperphosphorylated tau, neurofibrillary tangles, neuroinflammation, and oxidative stress. The renin-angiotensin system (RAS) plays a multifaceted role in the brain, with elevated levels of Angiotensin II (Ang II) and the up-regulation of angiotensin-converting enzyme (ACE) and angiotensin-1 (AT1) receptors being potential contributors to AD. ACE inhibitors such as Captopril, Fosinopril, Lisinopril, Perindopril, Trandolapril, and Zofenopril, along with angiotensin receptor blockers (ARBs) such as Azilsartan, Candesartan, Telmisartan, and Valsartan, are capable of crossing the blood–brain barrier. Pre-clinical and clinical studies have demonstrated that these RAS inhibitors exhibit anti-Aβ plaque, anti-tauopathy, free radical scavenging, and anti-inflammatory activities, making them highly reliable and effective potential therapeutic approaches for AD.
Keywords: ACE inhibitors, Angiotensin II (Ang II), AT1 receptor blockers (ARBs), anti-inflammatory, antioxidant, memory